Correcting the Theory of the Origin of Life with the Verses of the Qur'an in the View of the Islamic Religion - Sugiyanta Sugiyanta; Ulil Amri Syafri; Hasby Indra (Pelopor Publikasi Akademika, 2023)
This article explores the reconciliation between the theory of the origin of life and the teachings of the Qur'an within the framework of Islamic religion. It investigates the potential compatibility between scientific theories and religious beliefs, particularly focusing on the Qur'an's verses related to the topic. By analyzing and interpreting these verses, the article aims to provide a corrected perspective on the origin of life, integrating scientific knowledge with religious understandings. The research presents an interdisciplinary approach, encouraging dialogue and discourse between science and religion, while offering insights into the Islamic viewpoint on this fundamental subject.